GREEN ACCOUNTING BERBASIS DEEP ECOLOGY DALAM MENUNJANG KEBERLANJUTAN PERUSAHAAN - Rohani, Dian Amalia Putri; Abdullah, Wahyuddin; Awaluddin, Murtiadi (ISAFIR: Islamic Accounting and Finance Review, 2023)
Abstract, The purpose of this study is to find out how the disclosure and meaning of green accounting based on deep ecology and to see how the reality of sustainability is reflected in the sustainability report of PT Vale Indonesia in 2021. This research type is a qualitative research using semiotic analysis of company’s sustainability report to look at the disclosure of green accounting based on deep ecology in supporting the company’s sustainability. The data is obtained from the sustainability report of PT Vale Indonesia in 2021. The data used as the object of analysis in the semiotic study is the text contained in the sustainability report. The results of this study indicate that PT Vale has reported its environmental performance in the form of a sustainability report, but the data provided has not fully covered real cost reporting. Regarding the concept of deep ecology, PT Vale makes it happen throught 3 stages, namely strategic planning, implementation and program evaluation. The application of deep ecology based on green accounting in realizing the company’s sustainability is marked by 3 sustainability indicators that have been achieved by the company, namely operational sustainability, environmental sustainability, and sustainability of existence. Abstrak, Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pengungkapan dan pemaknaan green accounting berbasis deep ecology serta untuk melihat bagaimana realitas sustainability (keberlanjutan) yang terefleksi dalam sustainability report PT Vale Indonesia Tahun 2021. Jenis penelitian ini adalah penelitian kualitatif dengan menggunakan analisis semiotika untuk mengungkap makna pada sustainability report perusahaan dengan melihat pengungkapan green accounting berbasis deep ecology dalam menunjang keberlanjutan perusahaan. Data diperoleh dari sustainability report PT Vale Indonesia Tahun 2021. Data yang dijadikan objek analisis dalam kajian semiotik adalah teks yang terdapat pada sustainability report. Hasil penelitian ini menunjukkan bahwa PT Vale sudah melaporkan kinerja lingkungannya dalam bentuk sustainability report akan tetapi data yang diberikan belum sepenuhnya melingkupi pelaporan biaya secara ril. Terkait konsep deep ecology, PT Vale mewujudkannya melalui 3 tahap yaitu perencanaan strategis, pelaksanaan serta evaluasi program. Penerapan green accounting berbasis deep ecology dalam mewujudkan keberlanjutan perusahaan ditandai dengan 3 indikator keberlanjutan yang berhasil diraih oleh perusahaan yaitu keberlanjutan operasional, keberlanjutan lingkungan, dan keberlanjutan eksistensi.